(untitled) (World Science, 2020)
The article considers the problems of road-climatic zoning of the territory of Ukraine. The shortcomings of the existing system and the need to update and improve it were justified. The purpose of work was formed and realized taking into account modern approaches to meteorological data processing and segmentation methods. The study is based on long-term observations of weather conditions throughout the country. Using the moisture-thermal regime calculation and analytical system, the collected static meteorological information was processed and tables of the initial data for further analytical processing were obtained. The paper describes the methodology of cluster analysis using as the main tool for the typification of territories and the allocation of morphologically homogeneous humid areas. The result of the work was the elaboration of a road and climatic zoning map under the wetting conditions of the road subgrade working layer.